SLANG WORDS FOUND ON “TO ALL THE BOYS ALWAYS AND FOREVER” MOVIE - I Wayan Adi Nugraha Nugraha; I Komang Sulatra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Slang is a variety of language used mainly by teenagers to communicate with group members in informal situations. This research aims at identifying slang words and categorizing the type of slang used in the film